LAJU INFILTRASI PADA PENGGUNAAN LAHAN DI IUPHKM DI HUTAN LINDUNG TANDUNG BILLA KELURAHAN BATTANG KECAMATAN WARA BARAT KOTA PALOPO - Asrul Asrul; Yumna Yumna; Srida Mitra Ayu (Universitas Andi Djemma Palopo, 2021)
The low infiltration rate causes most of the rainwater that falls to the ground to become surface runoff, and only a small portion of the water can enter the ground as groundwater storage. The infiltration in the Tandung Billa IUPHKm location includes the use of forest land, shrubs, and mixed gardens, and the management carried out by the community at the Tandung Billa IUPHkm location is the cultivation of agricultural/plantation crops under tree stands in hilly or slightly sloping areas. Land use in the Tandung Billa Community Forest Utilization Business Permit (IUPHKm) consists of forest land, shrubs, and mixed gardens; each land use affects soil and land conditions, which in turn will affect the infiltration rate of the land. Therefore it is necessary to know how the infiltration rate in forest land use, mixed garden shrubs. Measurement of the infiltration rate was carried out by taking soil samples for physical properties, and soil moisture content in three different land uses, namely forest, shrub, and mixed garden land use; the measurement was carried out using a double-ring infiltrometer. The results showed that the infiltration rate on forest land was classified as medium-fast, namely = 83 mm / hour, with clay texture, then the infiltration rate in shrubland was classified as moderate, namely = .62 mm / hour, with clay soil texture and clay. The infiltration rate in mixed garden land/agroforestry is classified as moderate, namely = 53 mm / hour with a dusty clay texture.